The Presence of Trihalomethanes and Haloacetic Acids in Tropical Peat Water - Yuniati Zevi; Muammar Qadafi; Suprihanto Notodarmojo (Journal of Engineering and Technological Sciences, 2022)
The presence of dissolved organic matter (DOM) in tropical peat water affects the appearance of trihalomethanes (THMs) and haloacetic acids (HAAs) in natural water sources. However, information about the presence of THM and HAA in tropical peat water is still limited. This study was conducted to determine the presence of THMs and HAAs in tropical peat water taken from a canal and a river in Riau Peatland, Indonesia, influenced by the seasons and the tides. DOM was measured by dissolved organic carbon (DOC) and UV254 absorbance. The presence of THMs and HAAs was determined based on total THM4 and HAA5 and correlated with chloride and bromide concentrations. The concentrations of chloride and bromide in the river water were higher than in the canal water because of tidal influence. Total THM4 in canal water reached 22.70 ± 0.90 and 10.78 ± 0.71 µg/L in the dry and rainy seasons, respectively, but only reached 16.64 ± 1.93 and 5.52 ± 0.05 µg/L in the river water. In contrast to THM4, total HAA5 in the river water was higher than in the canal water and reached 104.01 ± 4.67 and 106.39 ± 9.53 µg/L in the dry and rainy seasons, respectively, but only reached 9.83 ± 0.48 and 56.87 ± 6.11 µg/L in the river water. THM4 predominated in the dry season while HAA5 predominated in the rainy season.